The Role of Internal Audit and Credit System in Delivering Company Profits (Case Study at PT Pegadaian (Persero) Sukabumi Branch) - Asri Noer Rahmi; Taufik Usman (Jurnal Ilmu Manajemen & Ekonomika, 2017)
This study aims to determine the role of internal audit and the credit system in delivery corporate profits on PT. Pegadaian (Persero) Branch Sukabumi. The variables used in this study is an internal audit, system of credit, and corporate profits. The method used in this research is descriptive. The scale used is ordinal scale. The population in this study were all employees at PT. Pegadaian (Persero) Branch Sukabumi. The data used are primary data and secondary data. Data were collected and analyzed using validity and reliability test, test the classical assumption of normality test, heteroscedasticity, multicollinearity test, and autocorrelation test, simple linear regression, hypothesis testing using t-test and F, and test the coefficient of determination. Validity test results showed that all the questions for the independent variables and the dependent variable are declared invalid. Reliability test results unreliable. The result of the classical assumption of normality test showed that the role of internal audit and the system of crediting of corporate profits distributed normally. The results of hypothesis testing (t-test) showed that t = 2,187> t table = 2,052 and 10,803 t count> t table 2,052. The results of the testing of F test shows that F count = 203.867> F tables 3,354. It can be concluded that the internal audit and the system of crediting contribute significantly to the company’s earnings. Results from test determination coefficient obtained by the magnitude of the role of internal audit and the system of credit to the company’s profit amounted to 93,8%. While the remaining 6,2% are influenced by other factors.